Studies of rare B hadron decays to leptons at hadron colliders - Chiochia Vincenzo (EPJ Web of Conferences, 2013)
Rare B hadron decays provide an excellent test bench for the Standard Model and can probe new physics models. We review the experimental progress of the searches for rare leptonic B decays (b → ℓ+ℓ− and b → sℓ+ℓ−) at LHC and Tevatron experiments.